2013
DOI: 10.1089/cyber.2012.0301
|View full text |Cite
|
Sign up to set email alerts
|

Can Facebook Use Induce Well-Being?

Abstract: Over the past few decades, the widespread phenomenon of Internet abuse has gained attention from the public, academia, and the media. In a departure from this negative viewpoint, however, researchers and educators have devoted considerable effort in attempting to understand the influence of online communication on people's psychological well-being. This study focuses specifically on Facebook, and proposes a research model to examine the relationships among Facebook use, online social support, general social su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(116 citation statements)
references
References 32 publications
3
96
0
9
Order By: Relevance
“…Moreover, research has shown that SNSs have the capacity to facilitate supportive interaction among adolescent users FACEBOOK USE, ONLINE SOCIAL SUPPORT, AND ADOLESCENTS' DEPRESSED MOOD 8 (Hampton, Goulet, Rainie & Purcell, 2011). As a result, studies began to examine the relationship between SNS use and people's perceptions of online social support (e.g., Liu and Yu, 2013). However, because not all SNS activities are equally "social", various scholars (e.g., Aubrey & Rill, 2013;Burke, Kraut, & Marlow, 2011) argue that different types of SNS use may produce different effects, and subsequently call for more differentiated analyses of SNS use.…”
Section: Active Facebook Use -Perceived Online Social Support -Depresmentioning
confidence: 99%
“…Moreover, research has shown that SNSs have the capacity to facilitate supportive interaction among adolescent users FACEBOOK USE, ONLINE SOCIAL SUPPORT, AND ADOLESCENTS' DEPRESSED MOOD 8 (Hampton, Goulet, Rainie & Purcell, 2011). As a result, studies began to examine the relationship between SNS use and people's perceptions of online social support (e.g., Liu and Yu, 2013). However, because not all SNS activities are equally "social", various scholars (e.g., Aubrey & Rill, 2013;Burke, Kraut, & Marlow, 2011) argue that different types of SNS use may produce different effects, and subsequently call for more differentiated analyses of SNS use.…”
Section: Active Facebook Use -Perceived Online Social Support -Depresmentioning
confidence: 99%
“…These service roles allowed me to watch the development of interesting research findings and theory development in the areas of social support, communication, and health, as well as computermediated communication. As time went on, scholars began to merge theory from both areas in an attempt to make stronger causal claims about the influence of social support network members on specific health outcomes (Han et al, 2012;Liu and Yu, 2013;Oh et al, 2014), by advancing and testing hypotheses stemming from these theoretical frameworks. Numerous extraneous variables and mediating variables have been identified, and they are now being controlled for in much of today's online social networks and health outcomes research.…”
Section: My Research Background In Social Support and Health Outcomesmentioning
confidence: 99%
“…Furthermore, Lui and Yu [15] used several wellness and social support measurements to identify whether there was a relationship between an individual's well-being and Facebook use by examining correlations between wellness, social support, online social support, gender, and intensity of Facebook use. Participants were a convenience sample of 400 college students with 330 students completing all survey information.…”
Section: Introductionmentioning
confidence: 99%